The Role of Journalists in Building Optimism in the Small Industry Community During the Corona Pandemic (Study: Formation of a Post For Journalists Covering Covid-19 for the South West Region of Aceh) - Muzakkir Muzakkir; Alisman Alisman; Putri Maulina; Ikhsan Ikhsan (Ilomata International Journal of Social Science, 2021)
The coronavirus pandemic has made some small industrial communities complain, plus there is confusing news information so that some people feel nervous in dealing with the spread of the coronavirus. The study in this research is basically field research (field research) and literary (library research), with a historical and multidisciplinary approach. Existing data, the authors analyze using a comparative method in a qualitative paradigm, through snowball sampling. Through this method, researchers hope to collect information needed by the small industrial community, so that they are motivated and enthusiastic in moving their business in the midst of the Corona pandemic. The role of the media is not only to report but also to deny hoax information and untrue information, moreover, the media has an important and strategic role in following the development of reliable information related to Covid-19 reporting, as a trusted source for the community towards the era of adaptation of new habits (new normal). ). The presence of journalists presenting news about aid programs, business opportunities, and product marketing facilities for small industry players in circulation and online is one of the breakthroughs that can foster new optimism and hope (expectations) among small industry players in the midst of their business slump due to the pandemic. corona. The final goal of this study, the author tries to get a concrete picture of the roles and responsibilities of journalists in building the optimism of the small industrial community during the corona pandemic.